Implementation Of Religious Values Through Islamic Education Learning At State Middle School 1 Surakarta - Oktaviani, Tri Ulfa; Abidin, Zaenal (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
The aim of religious values education is so that the younger generation has a noble personality and sufficient knowledge to live life. Character education is capital in responding to problems in the surrounding environment. To achieve this goal, it is necessary to have efficient methods and extraordinary processes. The data collected in this research was collected through observation, interviews, and documentary studies. The methodology used to analyze the data is the Maile Huberman method, which includes collecting, reducing, conveying, and drawing conclusions from the data. The results of the research show that students at SMP Negeri 1 Surakarta apply religious values in religious learning, namely, planning in the form of a syllabus and lesson plans which contain learning plans such as methods, approaches, media and sources used for learning religious values at SMP Negeri 1 Surakarta. There are also several challenges in the world of education, the problem is that the education system is still weak, its objectives are still unclear, the curriculum is not yet aligned, or relevant, the atmosphere is not yet attractive, and so on. Therefore, the figure of a PAI teacher is important in shaping students to change attitudes or habits that are considered inappropriate. The instillation of students' religious values at SMP Negeri 1 Surakarta states that the implementation of students' religious values is in the form of habituation to worship through congregational midday prayers, character education, reading the Koran before learning, especially during character education and PAI learning, other habits are about morals. There are obstacles to implementing religious values in an educational institution. The obstacle is from the students themselves, the lack of educators who can direct their students. The obstacle for teachers in introducing religious values is students whose character is difficult to change before school. Keywords: Religious Values, PAI Learning.